The Effect of Transformational Leadership on Employee Performance with Employee Engagement and Job Satisfaction as Moderator Variables - Wardani, Andrie; Baihaqi, Baihaqi; Nohong, Mursalim (Journal Research of Social Science, Economics, and Management, 2025)
Transformational leadership plays a strategic role in enhancing organizational effectiveness through a leader’s ability to inspire, motivate, and foster employee innovation. This leadership style is highly relevant for implementation in the BPS-Statistics Indonesia (BPS), a government institution oriented toward public service. This study aims to analyze the effect of transformational leadership on employee performance with work engagement and job satisfaction as moderating variables. It adopts a sustainable transformation approach, which is rarely addressed in previous studies that mainly focus on the direct impact of leadership on performance or employee motivation. In contrast to earlier research largely conducted in the private sector, this study offers specific contributions on the application of transformational leadership within governmental bureaucracy. Based on responses from 268 employees of BPS in West Papua Province and analyzed using Structural Equation Modeling (SEM), the findings reveal that transformational leadership has a positive and significant effect on employee performance. However, work engagement was found to weaken this influence, while job satisfaction strengthens the relationship between transformational leadership and performance.